2013
DOI: 10.1371/journal.pone.0070783
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota Composition of Interleukin-10 Deficient C57BL/6J Mice and Susceptibility to Helicobacter hepaticus-Induced Colitis

Abstract: The mouse pathobiont Helicobacter hepaticus can induce typhlocolitis in interleukin-10-deficient mice, and H. hepaticus infection of immunodeficient mice is widely used as a model to study the role of pathogens and commensal bacteria in the pathogenesis of inflammatory bowel disease. C57BL/6J Il10−/− mice kept under specific pathogen-free conditions in two different facilities (MHH and MIT), displayed strong differences with respect to their susceptibilities to H. hepaticus-induced intestinal pathology. Mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 70 publications
4
92
0
Order By: Relevance
“…The microbiota was analyzed as detailed by Yang et al (30) with modifications. Bacterial DNA was isolated using the QIAamp DNA stool kit (Qiagen, Hilden) according to manufacturer's instructions.…”
Section: S Rdna Microbiota Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The microbiota was analyzed as detailed by Yang et al (30) with modifications. Bacterial DNA was isolated using the QIAamp DNA stool kit (Qiagen, Hilden) according to manufacturer's instructions.…”
Section: S Rdna Microbiota Analysismentioning
confidence: 99%
“…After subsampling to an equal number of sequences per sample, rarefaction curves were generated with mothur. The distribution of OTUs among the samples was visualized using the R script heat map (36) as described by Yang et al (30). The R package vegan (37) was used for principal coordinates analyses (PCoA), using the "capscale" command in combination with the Bray-Curtis dissimilarity index, and for fitting the factors mouse genotype, litter, and mouse sex onto the PCoA ordination using "envfit."…”
Section: S Rdna Microbiota Analysismentioning
confidence: 99%
“…For example, Yang et al found that H. hepaticus could induce colitis in IL10 −/− mice bred at only one of two breeding facilities, and this trait was associated with a distinct intestinal microbiota in uninfected mice. 39 A complex gut microbiota has also been associated with enhanced clearance of H. felis, another gastric helicobacter. 40 However, studies performed by us and others that have looked for similar vendor or antibiotic effects on H. pylori colonization have met with negative results.…”
Section: Does the Gastric Microbiota Change H Pylori Colonization Ormentioning
confidence: 99%
“…C57BL/6J IL-10 2/2 mice held in different facilities and kept under specific pathogen-free conditions showed a significant difference in susceptibility to an H. hepaticus infection seemingly associated with their microbiota composition. 30 Another study shows that different laboratory diets influence susceptibility to DSS colitis. Each of the diets cause a different microbiota composition, which results in varying susceptibilities.…”
Section: Discussionmentioning
confidence: 99%